The World of Manufacturing : Industrial Arts Curriculum Project - Ohio State University Research Foundation; Ohio State Univ., Columbus. Research Foundation (Illinois : Mcknight and Mcknight, 1971)
This textbook for junior high school students encompasses concepts found in manufacturing, and together with a teacher's guide (VT 014 238) and laboratory manual (VT 014 239) constitutes the second part of a 2-year integrated program in industrial technology. This and the first year course in construction technology, were developed under contract to the U.S. Office of Education. The material was written by professionals in the manufacturing field, and is intended to give firsthand knowledge about the man-made world and enable students to view their world with greater understanding, appreciation, and insight. Sample topics included in the 82 are: (1) Manufacturing and the Economic System, (2) Building the Production Prototype, (3) Employment and Occupations in Manufacturing, (4) Converting Raw Materials to Industrial Materials, (5) Making Assemblies or Finished Parts, (6) Locating the Plant and Securing Inputs, and (7) Arranging for Distribution and Sales. There is extensive use of pictures and drawings for illustrations. Related documents are available as VT 014 088 and VT 014 241-VT 014 244. (GEB)
Availability: McKnight and McKnight Pub. Co., Route 66, Bloomington, Ill. 61701 ($7.96 list price).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
ERIC Note: Fourth Edition.
Educational level discussed: Secondary Education.
Keywords: Career Education; Career Guidance; Concept Teaching; Fundamental Concepts; Industrial Arts; Industry; Instructional Materials; Manufacturing Industry; Occupational Information; Resource Materials; Secondary Education; Study Guides; Technology; Textbooks; Industrial Arts Curriculum Project